USH2A Gene Editing Using the CRISPR System - Carla Fuster-García; Gema García-García; Elisa González-Romero; Teresa Jaijo; María D. Sequedo; Carmen Ayuso; Rafael P. Vázquez-Manrique; José M. Millán; Elena Aller (Elsevier, 2017)
Usher syndrome (USH) is a rare autosomal recessive disease and the most common inherited form of combined visual and hearing impairment. Up to 13 genes are associated with this disorder, with USH2A being the most prevalent, due partially to the recurrence rate of the c.2299delG mutation. Excluding hearing aids or cochlear implants for hearing impairment, there are no medical solutions available to treat USH patients. The repair of specific mutations by gene editing is, therefore, an interesting strategy that can be explored using the CRISPR/Cas9 system. In this study, this method of gene editing is used to target the c.2299delG mutation on fibroblasts from an USH patient carrying the mutation in homozygosis. Successful in vitro mutation repair was demonstrated using locus-specific RNA-Cas9 ribonucleoproteins with subsequent homologous recombination repair induced by an engineered template supply. Effects on predicted off-target sites in the CRISPR-treated cells were discarded after a targeted deep-sequencing screen. The proven effectiveness and specificity of these correction tools, applied to the c.2299delG pathogenic variant of USH2A, indicates that the CRISPR system should be considered to further explore a potential treatment of USH. Keywords: Usher syndrome, USH2A, c.2299delG, CRISPR, gene editing, RNPs